Aerodynamic evaluation of surgical design for the stenosis correction of airway - Bao, Wenjie; Liao, Andi; Yu, Pingping; Shen, Juanya; Zhao, Wenjing; Ding, Lifeng (Frontiers in Cardiovascular Medicine, 2024)
Congenital tracheal stenosis (CTS) is a rare but life-threatening disease, which can lead to respiratory dysfunction in children. Obstructive sleep apnea syndrome (OSAS) in children is characterized by prolonged partial upper airway obstruction and/or intermittent complete obstruction. Both of the diseases require surgical intervention. Although respective treatments of these two diseases are clear, the literature discussed the surgical treatment of patients of CTS complicated by OSAS is in deficiency.We conducted a patient-specific study of patient of CTS complicated by OSAS. Computer-aided design (CAD) was used to simulate surgical correction under different surgical sequence. Computational fluid dynamics (CFD) was used to compare the outcomes of different sequence. Aerodynamic parameters, pressure drop, velocity streamlines, wall shear stress, , the ratio of airflow distribution and energy loss, were evaluated. An obvious interaction was found between the two diseases in different surgical sequence. The order to correct the stenosis of CTS or OSAS greatly affected the aerodynamic parameters and turbulence flows downstream of tracheal stenosis and upstream of the epiglottis. The CTS and OSAS had mutual influences to each other on the aerodynamic parameters like pressure drops, WSS. When evaluating the priority of surgical urgency of CTS and OSAS, surgeons need to pay attention to the state of both CTS and OSAS and the physiological conditions of patients. The aerodynamic performance of aggravating the uneven airflow distribution caused by the correction of CTS and its potential effects should be considered in surgery planning and clinical management.